Self-regulated learning and engagement through emergency remote teaching in EFL undergraduate students - Oportus-Torres, René; Contreras-Soto, Yasmina; Sanhueza-Campos, Cristian; Maluenda-Albornoz, Jorge; Pérez-Villalobos, Christian; Quintanilla-Espinoza, Angie (Frontiers in Education, 2024)
Introduction An important concern of research about self-regulated learning is to determine the most effective methods for its instruction in different educational settings. This also happens in foreign language learning as improving proficiency is challenging for students and self-regulation has proven effective in different educational levels. Methods A quasi-experimental study was designed with a treatment and a control group, and pre- and post-test for 70 undergraduate students majoring in English as a foreign language at a Chilean university. A 10-week intervention was conducted to develop self-regulation during emergency remote teaching. Results Findings revealed that the intervention, as implemented in the study, was successful in improving self-regulated learning, and in participants’ recognizing the practical utility of tools acquired. On the other hand, while the level of engagement remained similar after the intervention, this was seen as a protective effect of the teaching-learning strategy on motivational states. Discussion This research underscores the importance of self-regulated learning training in higher education to allow for students’ autonomy and agency, as well as connectedness with instructors and peers, especially during the harsh teaching conditions of sanitary confinement.